2015
DOI: 10.1016/j.sleh.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The association of neighborhood characteristics with sleep duration and daytime sleepiness

Abstract: Background Neighborhood characteristics have been linked to health outcomes. Various mechanisms link neighborhoods and health outcomes; sleep patterns may be 1 contributor; however, little is known about the social determinants of disordered sleep. We examined the association of neighborhood characteristics with sleep duration and daytime sleepiness. Methods Participants (n = 801) enrolled as pairs (55 without pair), from 10 churches in the Stroke Health and Risk Education project; 760 were included for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 42 publications
2
37
0
1
Order By: Relevance
“…These findings are consistent with previous studies that reported an association between short sleep duration and low neighborhood safety. [10][11][12][13][14][15][20][21][22] These prior studies however, relied on self-reported sleep duration, raising concern that the associations might reflect known systematic biases in the accuracy of self-report, rather than an actual effect on sleep per se. Our results demonstrate that the perception that one lives in an unsafe neighborhood is associated with an objective measure of short sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previous studies that reported an association between short sleep duration and low neighborhood safety. [10][11][12][13][14][15][20][21][22] These prior studies however, relied on self-reported sleep duration, raising concern that the associations might reflect known systematic biases in the accuracy of self-report, rather than an actual effect on sleep per se. Our results demonstrate that the perception that one lives in an unsafe neighborhood is associated with an objective measure of short sleep.…”
Section: Discussionmentioning
confidence: 99%
“…11,[15][16][17][18][19] However, a major limitation of the existing literature linking adverse neighborhood features such as crime and violence with sleep has been the reliance on unvalidated measures of sleep. [10][11][12][13][14][20][21][22] While studies using actigraphy have evaluated the relationship between sleep and noise, these studies have been limited by small sample size, in-laboratory testing or low levels of noise that may limit generalizability of findings. 23,24 Our goal was to evaluate the relationship between neighborhood environment and validated measures of sleep in a large cohort of US Hispanics/Latinos, the largest racial/ethnic minority group in the United States and a group with a high prevalence of cardiovascular disease risk factors such as diabetes, obesity, and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature on neighborhoods and sleep has shown that self-reports of neighborhood safety and quality are associated with several sleep outcomes, including duration (DeSantis et al, 2013), efficiency (Bagley, Tu, Buckhalt, & El-Sheikh, 2016), daytime sleepiness (Johnson, Brown, Morgenstern, Meurer, & Lisabeth, 2015), and overall sleep quality (Hale et al, 2013; Hill et al, 2016). However, very few studies have considered objective measures of neighborhood disadvantage.…”
mentioning
confidence: 99%
“…Because of its influence on metabolic and cardiovascular processes (12) and links to depressive symptoms and suicide (13, 14), sleep could also serve as an important, understudied mechanism through which neighborhood contexts influence poorer physical and mental health (1518). …”
mentioning
confidence: 99%